Guidelines for using antimicrobials in veterinary surgery - Silva, J. L. P.; Castro, B. G.; Faria Júnior, D. (Scientific Electronic Archives, 2020)
The indiscriminate use of antimicrobials in clinical and surgical routine is an upward reality among veterinarians. The emergence of multiresistant strains is one of the consequences of the irrational use of these drugs, causing an emergency worldwide health problem. By 2050, it is estimated that superbugs will kill about 10 million people worldwide, more than cancer. This paper aims to conduct a literature review on the topic and raise awareness of health professionals about the importance of rationality in the act of choosing the antimicrobial to be used, as well as assess the need or not to use them